Swine influenza A replicon particle and live attenuated influenza virus vaccines induce differential systemic and mucosal antibody and T cell responses - Wymore Brand, Meghan; Kaplan, Bryan S.; Souza, Carine K.; Wiarda, Jayne E.; Kimble, J. Brian; Arruda, Bailey; Perez, Daniel R.; Baker, Amy L. (Frontiers in Veterinary Science, 2026)
Influenza A virus (IAV) in swine is a significant economic concern, and there is a critical need to improve vaccine efficacy. Commercial and experimental vaccine platforms are effective against homologous infection but may not reliably provide protection against drifted or heterologous viruses. Live attenuated influenza A virus (LAIV) vaccines induce mucosal antibody and localized cellular immune responses that may provide partial protection from drifted IAV. However, limited data exist on the induction of mucosal antibody and cellular immune responses and heterologous protection induced by RNA-based vaccines in swine. In this work, experimental, non-adjuvanted hemagglutinin-based replicon particle (RP-HA), and live attenuated influenza A virus (LAIV) vaccines were assessed for induction of mucosal antibody, cellular immune responses, and heterologous protection. LAIV reduced viral shedding and viral lung load while RP-HA limited macroscopic lung lesions. Both vaccines induced similar homologous systemic antibody and mucosal IgG, while only LAIV induced high levels of mucosal IgA. Both vaccines stimulated ex vivo virus-specific T cell proinflammatory cytokine production and proliferation. LAIV induced greater CD8+ T cell responses in the blood and the lungs, and CD4+ T cells in the blood, though RP-HA induced higher lung CD4+ T cell cytokine responses. Together, these results demonstrate that LAIV and RP-HA IAV vaccines induce differential antibody and T cell responses that are likely impacted by vaccine platform and route of exposure. A better understanding of correlates of protection, such as cellular immunity and mucosal antibody induction, will aid in the development of improved swine IAV vaccination strategies.